EARLY AND LONG TERM PREDICTIVE VALUE OF CARDIAC MARKER TROPONIN T AND CK-MB IN ACUTE MYOCARDIAL INFARCTION - Rashid, Shazia; Khawaja, Tariq Feroz; Khurshid, Rukhshan (Pakistan Journal of Physiology, 2010)
Background: Cardiac markers in serum are measured in the early hours after the onset of symptoms not to detect Acute Myocardial Infarction (AMI) but to exclude MI. To rule out AMI, one frequently must rely on the measurement of cardiac enzymes or biochemical markers when patients suspected of AMI present with atypical chest pain or a non-diagnostic ECG. We studied the levels of troponin T, and CK-MB in ruling out AMI in a group of patients in the first 24 hours after the onset of chest pain in the emergency room. Methods: Twenty male and 10 female patients in the first 24 hours after the onset of chest pain in the emergency room were included in the study. Patients with chest pain suggestive of myocardial ischemia within 12 hours after the onset of symptoms were eligible for the study, and all gave informed consent before inclusion. 5 males and 5 females with ruling out AMI were considered as controls. Levels of cardiatroponin T (cTnT) and CK-MB were estimated by standard kits. Results and Conclusion: Troponin T had a high sensitivity for MI when used as part of a rapid rule-in protocol; however, the use of TnT alone failed to identify the majority of patients and there is a need of CK-MB who had either significant disease or complications. We suggest that in diagnosis of patients with chest pain, both CK-MB and cTnT measurements should be performed on admission to the hospital with duration of chest pain 2–10 hours.